Wastewater pandemic preparedness: Toward an end-to-end pathogen monitoring program - Clark, Justin R.; Terwilliger, Austen; Avadhanula, Vasanthi; Tisza, Michael; Cormier, Juwan; Javornik-Cregeen, Sara; Ross, Matthew Clayton; Hoffman, Kristi Louise; Troisi, Catherine; Hanson, Blake; Petrosino, Joseph; Balliew, John; et al. (Frontiers in Public Health, 2023)
Molecular analysis of public wastewater has great potential as a harbinger for community health and health threats. Long-used to monitor the presence of enteric viruses, in particular polio, recent successes of wastewater as a reliable lead indicator for trends in SARS-CoV-2 levels and hospital admissions has generated optimism and emerging evidence that similar science can be applied to other pathogens of pandemic potential (PPPs), especially respiratory viruses and their variants of concern (VOC). However, there are substantial challenges associated with implementation of this ideal, namely that multiple and distinct fields of inquiry must be bridged and coordinated. These include engineering, molecular sciences, temporal-geospatial analytics, epidemiology and medical, and governmental and public health messaging, all of which present their own caveats. Here, we outline a framework for an integrated, state-wide, end-to-end human pathogen monitoring program using wastewater to track viral PPPs.